A web of canopy discoveries part I (Araneae: Araneidae). New astonishing species of orb-weaving spiders from Ecuador and the first country record of Pozonia Schenkel, 1953 - Díaz-Guevara, David R.; Dupérré, Nadine (Zootaxa, 2025)
Two new species from the family Araneidae are described: a new species from the monotypic orb-weaving genus Spinepeira Levi, 1995, Spinepeira erwini sp. nov. (♀), and a new species of Scoloderus Simon, 1887, Scoloderus neilli sp. nov. (♀), are described from the Ecuadorian Amazon. Both species were collected with insecticidal canopy knockdown. Furthermore, herein, we present the first images of Spinepeira’s internal genitalia, and the first country record of Pozonia Schenkel, 1953 is reported with Pozonia bacillifera (Simon, 1897) collected in the canopy of Tiputini in Ecuador.